The effect of spirituality on social entrepreneurship from Islamic perspective - Mhd. Sarif, Suhaimi; Ismail, Yusof (2013)
Spirituality in social entrepreneurship has formed a considerable awareness among the Muslim scholars in recent times. Although much scholarly work exists regarding spirituality, however, most were carried out from the western perspective. Previous Social entrepreneurship literatures has been based on behavior, intentions, and contextual variables and ignores or subordinates spiritual concepts. As social entrepreneurship includes innovative programs to improve livelihood to those who have no financial power, thus, it is the duty of the Muslim entrepreneurs to take initiative and innovate social security to satisfy the needs of the society. Realizing the current situation regarding spirituality in Islam and its effects on entrepreneurial outcomes, this exploratory study aims to explore how spirituality effects on social entrepreneurship from Islamic perspective which continue to create meaning for the Muslim entrepreneurs. Based on literature, propositions were developed on the effects of spirituality in Islam in relation to social entrepreneurship which need to be explored further.